2006
DOI: 10.1080/14672710600671087
|View full text |Cite
|
Sign up to set email alerts
|

History, identity, and security: Producing and consuming nationalism in China

Abstract: Chinese nationalism has ignited much debate among academics and the general public in both China and the West. Rather than search for the true core of Chinese nationalism, this essay will examine the curious custom of National Humiliation Day as an oblique entry into the politics of identity. The nation is not simply a question of people or territory, the author contends, but of time: the national time scripted by events such as National Humiliation Day. By comparing the differing practices of the holiday as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…To make concessions [and appear soft] would leave leaders open to charges of selling out sovereignty, which is political suicide in the Chinese system" [43], p. 190). 4 Based on interviews with Chinese analysts of the government and the military, Thomas Christensen concurs that the Chinese Communist Party "must be even more Chinese" because it is not communist any longer and nationalism is the only ideology that unites the people and props up the party's legitimacy; China's realpolitik, he contends, largely operates on its "historical legacies and national perceptions" [8], p. 41 and p. 46).…”
Section: Chinese Nationalism and Foreign Policy -Is Constructivist Pementioning
confidence: 96%
See 1 more Smart Citation
“…To make concessions [and appear soft] would leave leaders open to charges of selling out sovereignty, which is political suicide in the Chinese system" [43], p. 190). 4 Based on interviews with Chinese analysts of the government and the military, Thomas Christensen concurs that the Chinese Communist Party "must be even more Chinese" because it is not communist any longer and nationalism is the only ideology that unites the people and props up the party's legitimacy; China's realpolitik, he contends, largely operates on its "historical legacies and national perceptions" [8], p. 41 and p. 46).…”
Section: Chinese Nationalism and Foreign Policy -Is Constructivist Pementioning
confidence: 96%
“…In China, along with the decline of Communist ideology, the Chinese Communist Party (CCP) launched the "Patriotic Education Campaign" in 1991 to highlight the history of "century of humiliation (bainian guochi)" in contrast to its ultimate victory over Western imperialists and Japan, which has effectively legitimized its domestic rule while "redirecting protest toward the foreigner as an enemy, as an external Other" [4], p. 186). 3 Consequently, its cooperative foreign policies are at the risk of being perceived "soft" and thus challenged by domestic nationalists, a dilemma of the CCP's politics of historical memory [51].…”
Section: Chinese Nationalism and Foreign Policy -Is Constructivist Pementioning
confidence: 98%
“…More specifically, the concern here is how certain Chinese texts (song lyrics) might be deployed to frame Chinese history and identity in the narrow terms of nationalism, thereby confining the possibility of defining Chineseness in other terms such as gender, class or regional spaces (Callahan 2006). While thinking how to theorize on the relation between Hong Kong popular culture and issues of Chineseness, I was reminded of the danger of theoreticism (Hall 1996;Wright 2003) Before embarking on such an inquiry, I want to elaborate on two points, which make my preference for an autobiographical approach more than a preference.…”
Section: Another Approachmentioning
confidence: 99%
“…Risking grand narratives of Chineseness presumably inherited by the Chinese, I tried to put the historical burden back to the individuals of today, to give the 'yellowness' your own name, your own shape. Second, recalling the xenophobic tendency in some older minzu gequ and in the construction of Chinese nationalism through a performance of victimhood by 'foreign' enemies (Callahan 2006), I tried to trouble the narrative with indirect references to past tyrants in Chinese history. For instance, one of the original chorus lines read: 'Yellow people, who buried you with the dead?'…”
Section: Re-nationalization Iv: Performative Acts (Ii) -Writing With mentioning
confidence: 99%
“…ernment's manipulation of historical issues for instrumental purposes (Barme 1993;Brittingham 2007;Callahan 2006;Coble 2007;Cohen 2002;Downs and Saunders 1998;Gries 2004;He 2007;Mitter 2000Mitter , 2003Reilly 2012;Shirk 2007;Wang 2008;Weiss 2008;Zhao 2004). Among the studies that examine the Chinese side, two major instrumental purposes are found in the Chinese government's manipulation of the anti-Japanese sentiment-domestic legitimacy and diplomatic strategy.…”
mentioning
confidence: 99%